Multitarget‐Directed Ligands Combining Cholinesterase and Monoamine Oxidase Inhibition with Histamine H3R Antagonism for Neurodegenerative Diseases. Issue 41 (1st September 2017) - Bautista‐Aguilera, Óscar M.; Hagenow, Stefanie; Palomino‐Antolin, Alejandra; Farré‐Alins, Víctor; Ismaili, Lhassane; Joffrin, Pierre‐Louis; Jimeno, María L.; Soukup, Ondřej; Janočková, Jana; Kalinowsky, Lena; Proschak, Ewgenij; Iriepa, Isabel; et al.
Abstract: The therapy of complex neurodegenerative diseases requires the development of multitarget‐directed drugs (MTDs). Novel indole derivatives with inhibitory activity towards acetyl/butyrylcholinesterases and monoamine oxidases A/B as well as the histamine H3 receptor (H3R) were obtained by optimization of the neuroprotectant ASS234 by incorporating generally accepted H3R pharmacophore motifs. These small‐molecule hits demonstrated balanced activities at the targets, mostly in the nanomolar concentration range. Additional in vitro studies showed antioxidative neuroprotective effects as well as the ability to penetrate the blood–brain barrier. With this promising in vitro profile, contilisant (at 1 mg kg −1 i.p.) also significantly improved lipopolysaccharide‐induced cognitive deficits. Abstract : Hitting multiple targets at once : The therapy of multifactorial disease conditions needs to address multiple targets, which is challenging particular for neurodegenerative diseases. Designing multitarget‐directed ligands that may cross the blood–brain barrier is a complex task. The small‐molecule ligands described herein affect four neurotransmitter‐catabolizing enzymes as well as the histamine H3 receptor as a procognitive G‐protein‐coupled receptor.